GafChromic® EBT3 films for patient specific IMRT QA using a multichannel approach. Issue 8 (December 2015) - Marrazzo, Livia; Zani, Margherita; Pallotta, Stefania; Arilli, Chiara; Casati, Marta; Compagnucci, Antonella; Talamonti, Cinzia; Bucciolini, Marta
Highlights: EBT3 were evaluated for pre-treatment patient specific quality assurance. A calibration with 5 dose points was found to be adequate. Results are improved with the introduction of a reference for calibration rescaling. We demonstrated the multichannel approach is superior to the single channel dosimetry. EBT3 films turned out to be a reliable tool for IMRT patient specific QA. Graphical Abstract: Abstract: Purpose: To evaluate EBT3 for pre-treatment patient specific quality assurance (QA). The method we propose combines the experience gained in our center with the guidelines of the protocol proposed by Lewis et al. in 2012. To compare the multichannel approach with the single channel dosimetry. Methods: Gafchromic® EBT3 films were irradiated both at linac and TomoTherapy and calibration curves were obtained. A series of irradiations with simple fields (uniform dose distributions on regular shaped targets) was performed. In a second stage, films were exposed to full clinical plans at linac (step and shoot IMRT and VMAT). At TomoTherapy dose maps were obtained for a clinical plan in three different coronal planes. Films were digitized using an Epson 10000XL scanner and FilmQA™ Pro software was employed for the analysis. Results: The measured calibration curves suggest that, at least for the two beams taken into account (6 MV linac and TomoTherapy), a single calibration can be successfully adopted for each film lot. The application of the multichannel optimization method strongly improves the results in terms of gamma passing rates of the comparison between measured and calculated maps. Conclusions: Up to now EBT films, although attractive, were not preferred for routine patient specific QA due to their complex and time consuming processing and to the challenging work of characterization. The application of the mentioned protocol, together with some additional precautions, and the adoption of the multichannel optimization dosimetry, make this detector a handy and reliable tool for patient specific QA.